Proactive strategy for long-term biological research aimed at low-dose radiation risk in Korea. (31st May 2018) - Seong, Ki Moon; Kwon, TaeWoo; Park, Jina; Youn, BuHyun; Cha, Hyuk-Jin; Kim, Yonghwan; Moon, Changjong; Lee, Seung-Sook; Jin, Young Woo
Abstract: Purpose: Since the 2011 Fukushima nuclear power plant accident, Korean radiation experts have agreed that reliable data on health risks of low-dose radiation (LDR) are needed to ease the anxiety of lay people. The intent of this study was to devise a sustainable biological program suited for the research environment in Korea and aimed at the health effects of radiation exposures <100 millisieverts (mSv). To address pressing public concerns over LDR risk, we investigated the current understanding of LDR effects by analyzing the previous reports of international authorities for radiation protection and research publications that appeared after the Chernobyl accident. A research program appropriate for societal and scientific inclinations of Korea was then devised based on input from Korean radiation scientists. Conclusions: After review by our advisory committee, program priorities were set, calling for an agenda that focused on dose-response relationships in carcinogenesis, health span responses to lifestyle variations, and systemic metabolic changes. Our long-term biological research program may contribute scientific evidence to reduce the uncertainties of LDR health risks and help stakeholders formulate policies for radiation protection.